Analisis Korelasi Berbagai Faktor Budidaya terhadap Produktivitas Nira Siwalan (Borassus flabellifer L.) di Kecamatan Semanding Kabupaten Tuban - Wahida, Afia Firna; Widiatningrum, Talitha; Kartijono, Nugroho Edi; Irsadi, Andin (Universitas Negeri Semarang, 2024)
Palmyra (Borassus flabellifer L.) is the identity plant of Tuban Regency. The main palmyra product in Tuban Regency is the sap. In the last 5 years (2015-2020) the productivity of sap has not increased. This study aimed to determine the correlation between cultivation factors and palmyra production in the Semanding Subdistrict, Tuban Regency, Indonesia. The research was correlative research with quantitative descriptive explanatory. The independent variables were several tree ownership, nurseries, fertilization, tapping methods, and control of plant pests. The dependent variable was the productivity of the palmyra sap. The research data sources were the people in the villages of Kowang, Gedongombo, Tegalagung, and Prunggahan, with a total sample taken of 103 people. Data collection was carried out using observation and semi-structured interviews. The results were then analyzed using the multiple linear regression application SPSS 25. The results showed that all the factors in the model, through the F test, had a significant effect simultaneously. Partially using the t-test, the factors that influence the productivity of the palmyra sap are pest control, the number of trees, and tapping methods. Therefore, the result confirmed the correlation between cultivation factors and palmyra production in the Semanding Subdistrict, Tuban Regency, Indonesia.